Educating managers to learn strategically on the job: Lessons from British managers - Kanda, Markoto; Kidd, John B. (Universiti Utara Malaysia, 1997)
We hypothesised that the best way of modifying managers' behaviour is by changing the processes involved in their making and implementing their own strategic plans. To obtain data we used a questionnaire (survey), which focused on the linkages between British senioors managers' behaviour. Specifically we studied the above processes from which we determined their chances of learning how to behave. The survey findings indicate the best principles for learning by managers; we can therefore suggest implications for structuring their strategic planning processes and their implementation. We propose how best to educate managers to be good learners.